Tax system and database design in Libya - Alatrest, Emhimed S. A. (İstanbul Kültür Üniversitesi / Fen Bilimleri Enstitüsü / Matematik ve Bilgisayar Bilimleri Anabilim Dalı, 2006)
The taxation system is considered one of the bases of any financial system all over the world. The tax is defined as (the amount of money that government earns obligatory through one of the general departments according to approved legal laws. Then it is apparent that tax is considered a financial tool through which earnings are transferred forming the private use to public usage, as it is the tool that extract a portion of individuals’ incomes or wealth, and transfer it to the governmental budget in order to accomplish its financial, economical and social objectives. The first taxation law in Libya has appeared in the Turkish era (Ottoman) as there were taxes earned on agricultural corps and commercial activities. These taxes are paid to the government in a form of gifts or donations presented by the individuals to the governing authority started to demand it by itself from the individuals whenever the government goes through economical crises and natural disasters and wars. Then tax has become regularly paid on constant bases, and then this elective contribution has been converted into a national duty which the society imposes through the government representing it. Thus individuals has become obliged to pay part of their incomes or wealth as their contribution to undertake governmental burden, and the obligation element in this stage requires the approval of the donors to pay the tax, but it was the government that imposed it by its open choice and bond its payers, then tax is not imposed any further, but it is demanded according to laws issued by the legislative authority representing the people which is supposed to authorize this government to impose taxes , that is what is called the consent principle , wasn’t but a game played by the governors and this tax 2 system has continued till 1968 and is considered the first integrated tax system applied in Libya till AlFATEH revolution . For the year 1973 . Subjected to judicial control on constitutionality of laws, which is still valid till the present time, with the addition of some amendments from time to time on this law in order to satisfy people’s need.
Keywords: Bilgisayar Mühendisliği Bilimleri-Bilgisayar ve Kontrol; Computer Engineering and Computer Science and Control